Análisis semiótico del cementerio de Riobamba como espacio de construcción social, periodo julio 2016- julio 2017 - Chávez Castro, Paola Carolina (2018)
The objective of this project is to determine the semiotic sense of the Riobamba cemetery as a space for social construction in the inhabitants of the Riobamba canton, as well as to identify the symbolic elements of the cemetery and also to semiotically analyze the signs and symbols of the Riobamba cemetery. The necropolises are the mirrors of the cities, there is reflected everything that makes up a city; from architecture to colors, everything communicates and everything represents something for someone. The social construction is formed through the day to day, the experiences and communication of people who interact with each other and in a given space; referring to authors like Jean Piaget, Levi - Strauss, Émilie Durkheimer, Adorno and Horkheimer who argue through the functionalist, structuralist and constructivist theories as important aspects of social construction, also to Charles Sanders Pierce and that through the theory of the signs replicates that man and everything that composes communicates to the outside. According to the applied methodology, the scientific, inductive - deductive and descriptive method helped us to verify and analyze the causes and effects of the variables proposed. The population to which the study is directed is to the inhabitants of the urban Riobamba canton, where surveys and interviews were applied to collect the necessary information and obtain results. Concluding that the Riobamba cemetery is a space for social construction. Finally, a triptych was drawn up identifying the representative spaces of the cemetery and its history since 1890.